Influence of the individual microstructural features on pitting corrosion in type 304 austenitic stainless steel. (September 2019) - Pradhan, S.K.; Bhuyan, P.; Mandal, S.
Graphical abstract: Highlights: Sensitized specimen exhibits remarkably lower resistance to pitting corrosion. Pits are preferentially nucleated at J0, J1 -type of triple junctions, and RHAGBs. Higher fraction of Σ3 n (n ≤ 3) boundaries hinders nucleation of pits in GBE-specimen. Higher RHAGBs surface area in fine-grained specimen impairs its pitting resistance. Residual strain predominantly lowers the pitting resistance of 304 stainless steel. Abstract: The individual role of microstructural features viz. grain boundary character distribution (GBCD), grain size and residual strain on pitting corrosion is assessed in type 304 stainless steel employing potentiodynamic and potentiostatic polarization tests. Greater fraction of Σ3 n (n ≤ 3) boundaries and J3 -type triple junctions have resulted in better pitting resistance in the optimized GBCD specimen. The presence of higher dislocation density in the deformed specimen has resulted in greater pit generation rate. The fine-grained microstructure has exhibited inferior pitting resistance due to its higher random high angle boundary surface area which serve as preferential sites for nucleation and growth of pits.